New Instruments for Financing Small and Medium Enterprises in Russia: Crowdinvesting - I. A. Ezangina; A. V. Evstratov (Финансы: теория и практика, 2019)
Access to financing is a fundamental factor determining growth opportunities for small and medium enterprises. Along with the state forms of support for the subjects of this business segment, as well as traditional banking products, private investment mechanisms are being developed through the establishment and extension of crowdinvesting platforms. They imply involving funds of population as the most important market agent. The aim of the article is to reveal the key importance of the institutional development of the crowdfunding and crowdinvesting market as a modern tool for supporting small and medium enterprises, reproduction of people’s personal savings and incomes of professional investors. The following scientific methods and approaches were used in the study: observation, comparison, analogies, analysis, synthesis, method of expert assessments, system and structured approach. The authors’ definition of crowdinvesting is given. Three fundamental features of crowdinvesting are defined: collective microfinancing of a project from an alternative set of startups, an intermediate agent in the form of a remote platform, financial retribution. To prove the development of the world and domestic crowdinvesting market, its condition and the performance indicators of well-known crowdinvesting companies are characterized in dynamics. The authors revealed the key advantages of crowdinvesting, factors stimulating of its volume growth in Russia, as well as risks, mainly associated with insufficient regulation of the new and fast-growing institutional mechanism of crowdinvesting. The important perspective of crowdinvesting as an instrument of project financing in Russia is highlighted on the example of specific scopes for investment, multifunctional services of Russian platforms, expanding pool of investors, new financial and technological methods of exchange and support. The study allowed identifying a number of key areas for crowdinvesting development in Russia. The work mainstreams: building an effective regulation system for crowdinvesting platforms, including through developing self-regulation tools, a co-financing program for crowdinvesting projects from development institutions, the work of the regulatory sandbox, legislative consolidation and support for implementing new types of information and economic interaction on crowdinvesting platforms (not only B 2B, P2B, but also G2B, B 2G).